Seasonal variation in reproductive problems of buffaloes under field conditions - TOMAR, K P S; SINGH, PAWAN; SINGH, RAJENDER; SINGH, SAJJAN (The Indian Journal of Animal Reproduction, 2023)
Seasonality in the reproductive disorders in buffaloes was studied on five years ( 1992-96) data collected frqm adopted villages of ND RI, Kamal. The year was divided into five seasons viz., winter, spring, summer, rainy and autumn. The reproductive disorders recorded were anestrus, repeat breeding, metritis, antipartum prolapse, post partum prolapse, abortion, dystocia and retention of placenta. The occurrence of reproductive disorders varied significaptly between seasons. The incidences of anestrus was maximwn among all the reproductive disorders value varied from 66. 73 to 55. 99 per cent, the minimum incidences were of dystocia which varied from .07 to 3. 92 per cent across the seasons. The maximum (66. 73%) cases of anestrus were in autumn and minimwn (55. 99%) in swnmer season. Among all the reproductive disorders the maximum incidences were of anestrus followed by metritis, retention of placenta, repeat breeding, antipartum prolapse, postpartum prolapse, abortion and dystocia. The maximwn occurrence of reproductive disorders was found in summer and rainy seasons. From the study it can be concluded that the anestrus was the main reproductive problem across the seasons and maximwn incidences of reproductive disorders were found in summer and rainy seasons in buffaloes under field conditions.